Analisis Peran Pembiayaan oleh Pegadaian Syariah bagi Pengembangan UMKM - Muhammad Fuad; Meilyda Trianna (IAIN Langsa, 2018)
Sharia pawnshops are part of non-bank financial institutions in Indonesia that function to distribute financing through lending money based on the principle of pawn to the business sector in need. UMKM is a business sector that mainly faces constraints on access to financing in the aspect of guarantee and legality and administrative procedures. The Ar-Rum product was launched by Sharia pawnshops using a fiduciary system, in the hope of assisting the needs of the business sector. This study aims to analyze how the role of Ar-Rum as financing product in the development of SMEs. Primary data were collected through questionnaires and interviews on 100 customers, then analyzed using descriptive and statistics methods. Descriptive analysis results show that the majority of respondents stated strongly agree or agree that Ar-Rum useful to help the development and sustainability of their business, while the results of statistical tests states that the Ar-Rum product positively and significantly influences on the development of SMEs.